Investigating influence of low fraction of polytetrafluoroethylene filler on mechanical and wear behavior of light-cured dental composite. (24th May 2019) - Sonal,; Patnaik, Amar; Kumar, Shiv Ranjan; Godara, Manish
Abstract: In this study, a novel polymer filler polytetrafluoroethylene was used in the fabrication and testing of dental composite. The effect of low content of polytetrafluoroethylene (0 wt%–9 wt%) on mechanical and wear behavior of dental composite was investigated. The mechanical behavior was studied using Micro-Hardness, Compressive strength, Dynamic mechanical analysis and Thermo-gravimetric analysis. The in vitro wear tests were performed on dental wear simulator by varying number of cycles, sliding speed, normal load and filler content. The finding of results indicated that composites with increased in polytetrafluoroethylene fillers exhibited better mechanical and wear properties and showed smoother worn surface in artificial saliva medium. The hardness and compressive strength of dental composite were increased by 54.32% and 13.36% respectively with the addition of 9 wt% polytetrafluoroethylene. The storage modulus and damping ratio were increased with the increase in polytetrafluoroethylene. In two-body abrasive wear, the wear rate of dental composite was increased with increase in the number of cycles, normal load and sliding speed. Apart from excellent aesthetic properties, PTFE slightly improved the mechanical and wear properties of dental material.